M-Clinic: mobile application system for UiTMT Health Center equipment reservation / Mohd Ridzuan Mat Yassin - Mat Yassin, Mohd Ridzuan (2012)
M-Clinic equipment reservation is a mobile application created for UiTM Terengganu Health Center use only. It allows user to make reservation of equipment available at UiTMT Health Center such as stick, wheelchair and First Aid Kit. Previous method is user has to go by themselves to the Health Center to make the reservation. M-Clinic system will make sure that the reservation entered by user using mobile will be send to the Health Center Database to be reviewed by the administrator. By doing this, user can do reservation and check their reservation only by mobile, they do not need to go to the Health Center unless to pick up the equipment reserved. It completes the objective of this project which is to determine the information needed to create the system for equipment reservation and information needed to mobilize the application. This system was develop in mobile platform using NetBeans by connecting to the database which is MySQL using tomcat server by creating the servlet. It involve three type of tiers which is Presentation Tier for the interface, Database Tier for centralize the data and information entered by the user and Business Tier which functions as connecter between the interface and the database. Besides, the needed of java such as J2ME helps to create the presentation tier for the mobile application interface.